Enlargement as a Special Case of EU External Differentiation - Lyudmila O. Babynina (Современная Европа)
The multi-format system of external differentiation of the European Union has existed for many decades. A special place in it is occupied by relations with candidate countries, which are built on the principles of conditionality and evaluation of “merits” in the process of implementing reforms, but at the same time require an update of the structure of the European Union itself. After 2022, this approach has been significantly transformed. The article analyzes the main parameters of changes in relation to enlargement after 2022, when geopolitical considerations began to prevail over the requirement to comply with EU rules. In order to give impetus to the integration of old and new candidate countries, the Commission presented the concept of gradual sectoral integration. From a geopolitical point of view, the proposed path may become a solution to the enlargement problem and will give candidate countries real advantages before full membership. But from a practical and institutional point of view, limited sectoral integration may conflict with the principles of the indivisibility of the functioning of the European Single Market (ESM) of the EU and replace the accession negotiations. It is concluded that the updated enlargement strategy, when implemented, will create a new format of external integration with a very complex governance structure and will lead to new challenges for the ESM and the EU as a whole.